ChemInform Abstract: Aaptoline A, a New Quinoline Alkaloid from the Marine Sponge Aaptos suberitoides. Issue 21 (27th May 2014) - Tsukamoto, Sachiko; Kudo, Yodai; Kato, Hikaru; Rotinsulu, Henki; Losung, Fitje; Mangindaan, Remy E. P.; de Voogd, Nicole J.
Abstract Title compound (I) is isolated, and a biosynthetic pathway is proposed.